Ilex malayana, a replacement name for Ilex macrophylla Wall. ex Hook.f., and its lectotypification (Aquifoliaceae) - Malek, Aliaa Athirah Adam; Pruesapan, Kanchana; Corlett, Richard T. (Phytotaxa, 2024)
N/A